2001
DOI: 10.1007/s00253-001-0848-9
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Bacillus subtilis (chungkookjang), a poly-?-glutamate producer with high genetic competence

Abstract: A bacterium with high poly-gamma-glutamate (PGA) productivity was isolated from the traditional Korean seasoning, Chung-Kook-Jang. This bacterium could be classified as a Bacillus subtilis, but sporulation in culture was infrequent in the absence of Mn2+. It was judged to be a variety of B. subtilis and designated B. subtilis (chungkookjang). L-Glutamate significantly induced PGA production, and highly elongated PGAs were synthesized. The volumetric yield reached 13.5 mg ml(-1) in the presence of 2% L-glutamat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
99
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(104 citation statements)
references
References 21 publications
4
99
0
1
Order By: Relevance
“…In the case of B. anthracis, the genes involved in c-PGA synthesis lie on a large plasmid, as opposed to other Bacillus species where the genes are present on the chromosome (Ashiuchi et al, 2001a;). …”
Section: C-pga Polymerizationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of B. anthracis, the genes involved in c-PGA synthesis lie on a large plasmid, as opposed to other Bacillus species where the genes are present on the chromosome (Ashiuchi et al, 2001a;). …”
Section: C-pga Polymerizationmentioning
confidence: 99%
“…The L-glutamic-aciddependent bacteria include B. subtilis (chungkookjang) (Ashiuchi et al, 2001a), B. licheniformis 9945a (Birrer et al, 1994) B. subtilis CGMCC 0833 , B. licheniformis NK-03 (Cao et al, 2010) and B. subtilis (natto) ATCC 15245 (Bhat et al, 2013), whilst the non-Lglutamic-acid-dependent producers include B. subtilis C1 (Shih et al, 2005), B. amyloliquefaciens LL3 (Cao et al, 2011) and B. subtilis C10 (Zhang et al, 2012). For Lglutamic-acid-dependent bacteria, the PGA yield increases with an increase in the L-glutamic acid concentration in the medium.…”
Section: Production Of C-pga By Microbial Fermentationmentioning
confidence: 99%
“…Recently, Bacillus subtilis sups. chungkookjang, isolated from chungkookjang, a traditional Korean fermented soybean food, was reported to produce ␥-PGA, a copolymer of Dand L-glutamate that has a higher molecular mass (Ͼ1000 kDa) than ␥-PGA (10 -10,000 kDa) produced from B. subtilis (natto) (2). Currently, we studied the antitumor effects of the high molecular mass ␥-PGA isolated from B. subtilis (chungkookjang) to determine whether this might be a source for an effective oral antitumoral agent and the basis underlying these effects.…”
mentioning
confidence: 99%
“…Park et al, 2001) are reported. Anti-obesity effects were reported in mice and rats fed with high fat diets (Ashiuchi et al, 2001;Choo, 2000;Koo et al, 2008); fermented kochujang supplementation of a high fat diet prevented obesity in mice by reducing fat deposition and decreased circulating levels of cholesterol, triglycerides, and blood glucose, mediated by downregulating expression of lipogenic enzymes and up-regulating the lipolytic enzymes and the thermogenesis gene UCP-1 (Koo et al, 2008).…”
Section: Kochujangmentioning
confidence: 99%